Kampanye Inklusivitas LGBT Disney: Analisis Konten Kualitatif dalam Film Strange World (2022) - Hamzah Tegar Ashari; Ali Nuke Affandy; Ngatma'in (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pembangunan Nasional Veteran Jakarta, 2024)
This research examines Disney's propaganda of the LGBT inclusivity through Strange World (2022) movie. Previous researchers agree that Disney has several times included propaganda of certain values in its films, such as feminism, racial issues, and world wars. Based on this, we assume that Disney also propagates the value of LGBT inclusivity that encourages acceptance of LGBT people at large, from their idealism to their communities. This research explores how Disney incorporates the value of LGBT inclusivity in the movie Strange World (2022) using a descriptive qualitative approach. This approach was chosen because it is able to present an in-depth understanding of LGBT representation in Strange World (2022). The primary data in this research is the film Strange World (2022) which is analyzed using Edo Kuckartz's qualitative content analysis (QCA) technique. The results showed that the LGBT campaign was carried out in the film Strange World (2022) by displaying LGBT representation manifestly and latently. The representation is shown through the homosexual pairing of the main character, Ethan Clade and Diazo, as well as the transvestite character, Caspian. Another form of the campaign is shown through the